A new species of Crinum (Amaryllidaceae) from the Eastern Ghats of Andhra Pradesh, India - Rasingam, Ladan; Susmitha, Goparaju; Ranjana, Jamuda; Ranjithkumar, Pasupula; Arikrishnan, Parthiban (Phytotaxa, 2024)
Crinum andhricum (Amaryllidaceae), a new species from the Northern Eastern Ghats of Andhra Pradesh is described and illustrated. It is closely related to Crinum amoenum and C. stracheyi, but differs in its number of flowers per inflorescence, shape of the perianth lobes and filament length.